Impacts of land use changes from the Hanoi Master Plan 2030 on urban heat islands: Part 1. Cooling effects of proposed green strategies. (July 2017) - Kubota, Tetsu; Lee, Han Soo; Trihamdani, Andhang Rakhmat; Phuong, Tran Thi Thu; Tanaka, Takahiro; Matsuo, Kaoru
Graphical abstract: Highlights: We assess UHI effects before and after the implementation of the Hanoi Master Plan 2030. The UHI effect due to the master plan becomes significant, especially at night. The proposed green strategies are not effective at cooling all of built-up areas. It is important to cool the hot westerly Foehn wind before entering the city. Abstract: Hanoi City, Vietnam, presented the Hanoi Master Plan 2030 in 2011 to cope with rapid population growth and urbanisation. The main objective of this two-part study was to investigate the impacts of land use changes from the master plan on urban climate in Hanoi by 2030. This paper focuses on the assessment of the proposed green strategies in the master plan. Firstly, numerical simulations using the Weather Research and Forecasting were conducted for the present land use condition as well as the condition proposed by the master plan under the same extremely hot summer conditions of June 2010. Secondly, the results of the master plan condition were further compared with other scenarios comprising different green strategies for assessing their cooling effects. Based on the results, the daytime peak air temperature in the master plan condition was projected to maintain almost the same level as the current condition. However, the high temperature areas with temperature of 40–41 °C, would expand widely over the planned built-up areas. Further results showed that the green strategies were not necessarily effective at cooling all of the built-up areas, though these strategies largely reduced the air temperature within the green spaces, particularly at night.